2011
DOI: 10.1007/s00277-011-1224-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thalidomide with melphalan and prednisone on health-related quality of life (HRQoL) in elderly patients with newly diagnosed multiple myeloma: a prospective analysis in a randomized trial

Abstract: Thalidomide with melphalan/prednisone (MPT) was defined as standard treatment in elderly patients with multiple myeloma (MM) based on five randomized trials. In one of these trials, HOVON49, a prospective health-related quality-of-life (HRQoL) study was initiated in order to assess the impact of thalidomide on QoL. Patients aged >65 years with newly diagnosed MM were randomized to receive melphalan plus prednisone (MP) or MPT, followed by thalidomide maintenance in the MPT arm. Two hundred eighty-four patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…23 In a trial testing the addition of thalidomide to melphalan plus prednisone in patients not suitable for ASCT, Verelst et al reported that despite more frequent and severe adverse events, patients receiving thalidomide reported superior emotional function and future perspectives with no differences detected in global scores, thus supporting a decision to adopt adding thalidomide to melphalan-prednisone as standard treatment based on demonstrated improvements in PFS and survival. 24 As with our trial, thalidomide was associated with poorer physical functioning, constipation, and paresthesias and less insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…23 In a trial testing the addition of thalidomide to melphalan plus prednisone in patients not suitable for ASCT, Verelst et al reported that despite more frequent and severe adverse events, patients receiving thalidomide reported superior emotional function and future perspectives with no differences detected in global scores, thus supporting a decision to adopt adding thalidomide to melphalan-prednisone as standard treatment based on demonstrated improvements in PFS and survival. 24 As with our trial, thalidomide was associated with poorer physical functioning, constipation, and paresthesias and less insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in HRQoL have previously been reported during treatment with melphalan, prednisone, lenalidomide followed by lenalidomide maintenance (MPR-R) in patients with NDMM, 39,43 and the addition of thalidomide to MP did not negatively affect HRQoL. 44 However, our results contrast with the HRQoL trade-off reported with bortezomib in the VISTA trial, which compared MPV versus MP in NDMM patients and in which MPV had superior PFS and OS efficacy, but where patients' HRQoL was significantly compromised, especially in the first four cycles of treatment. 45,46 In the FIRST trial, although HRQoL was improved and maintained during the progression-free state, it deteriorated when disease progression occurred, regardless of the treatment received.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of PNP has been shown to increase with prolonged use of thalidomide, rising to > 50% (grade ≤ 2 in most patients) after 1 year of treatment [39]. A prospective analysis comparing MP versus MPT followed by thalidomide maintenance in the MPT arm showed that the higher frequency of toxicity associated with MPT does not translate into a negative effect on health-related quality of life and that MPT treatment holds a better patient perspective in elderly patients with newly diagnosed MM [40]. Consensus guidelines for the optimal management of AEs in newly diagnosed MM patients who are older than 65 years or transplant ineligible recommend clinical assessment of the patients prior to and at regular intervals during treatment with MPT.…”
Section: Phase III Studiesmentioning
confidence: 99%